Guide to Discrete Mathematics An Accessible Introduction to the History, Theory, Logic and Applications - O'Regan, Gerard (Texts in Computer Science,, 2016)
This stimulating textbook/reference presents a broad and accessible guide to the fundamentals of discrete mathematics, highlighting how the techniques may be applied to various exciting areas in computing. The text is designed to motivate and inspire the reader, encouraging further study in this important skill. Topics and features: Provides an introduction to the building blocks of discrete mathematics, including sets, relations and functions Describes the basics of number theory, the techniques of induction and recursion, and the applications of mathematical sequences, series, permutations, and combinations Presents the essentials of algebra, covering simultaneous and quadratic equations, and the laws of logarithms and indices, in addition to such structures in abstract algebra as monoids, groups, rings, integral domains, fields, and vector spaces Explains the fundamentals of automata theory, matrices, graph theory, cryptography, coding theory, language theory, and the concepts of computability and decidability Reviews the history of logic, discussing propositional and predicate logic, as well as such advanced topics as fuzzy logic, temporal logic, intuitionistic logic, undefined values, theorem provers, and the applications of logic to AI Examines the important field of software engineering, describing formal methods, including the Z specification language Investigates probability and statistics, covering discrete random variables, probability distributions, sample spaces, variance and standard deviation, and hypothesis testing This engaging and clearly written work offers an invaluable overview of discrete mathematics for undergraduate computer science students, and to students of mathematics interested in the rich applications of discrete mathematics to the field of computing.